Studying sexuality: LGBTI experiences in institutions of higher education in Southern Africa - Nduna, M.; Mthombeni, A.; Mavhandu-Mudzusi, A.H.; Mogotsi, I. (South African Journal of Higher Education, 2017)
Although there are several studies internationally on gender and sexual orientation diversity, these are limited in the Southern African Development Communities’ (SADC). This special issue contains articles written from different Institutions of Higher Education (IHE) in the SADC region on experiences of LGBTI individuals covering sexual health, teaching and training, advocacy and interventions. The aim of publishing this research is to disseminate information for broader advocacy to destabilise hetero- and cis-normativity. The study sites included rural and metropolitan-based institutions and diverse research designs were used. Most of the research findings presented here indicate that the institutions of higher education in SADC are still heteronormative and LGBTI staff and students are marginalized, prejudiced and discriminated against. Some studies report that there are activities in a few institutions harnessed in order to create conducive teaching and learning environments for and about sexual orientation and gender identity in the SADC.